Chemical tracer transport in the eastern boundary current system of the North Atlantic - M Álvarez; XA Álvarez-Salgado (Ciencias Marinas, 2009)
The MedBox region, comprising the Strait of Gibraltar to 22ºW and from 24ºN to 41ºN, has been defined using thermohaline and chemical data from three WOCE cruises conducted in 1997/98. The water mass structure of the region was objectively solved by an extended optimum multiparameter (OMP) analysis. Volume transports were estimated from field data and an inverse box model that ensures volume conservation and no deep water formation within the region. The combination of the volume transports, the OMP water mass analysis, and the distributions of chemical parameters allowed for the assessment of the oxygen, inorganic carbon, nitrate, phosphate, and silicate transport mechanisms, their vertical and lateral variability, and the relative contribution of the different water masses in the mid-latitudes of the eastern North Atlantic to these transports. La región MedBox comprende desde el Estrecho de Gibraltar hasta 22ºW y entre 24ºN y 41ºN.